2022
DOI: 10.1002/adom.202201682
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Nanoparticle Arrays Guided by Ordered Nanowire Films Enhance Surface‐Enhanced Raman Scattering

Abstract: platforms with high sensitivity to identify the presence of toxic substances. [8][9][10] Currently, plasmonic metals gold (Au), silver (Ag), and copper (Cu), have extensively been exploited as SERS platforms mainly due to their significantly enhanced Raman signal at the nanoscale evolved from their plasmonic features. [11][12][13] These metal nanoparticles could be easily assembled to improve their performance, [14][15][16][17] and effectively control the detected signal intensity by regulating the intrinsic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The enhancement factor was 10 5 and 10 9 for 2,4-dinitrotoluene and Rhodamine 6G, respectively. Recently, Sheng et al [104] have fabricated ordered LB TeNWs film to further immerse in HAuCl 4 aqueous solution. After the reduction, the ordered Te-Au hetero NWs film was tested as a SERS substrate.…”
Section: One-dimensional Materials (Nanowires and Carbon Nanotubes)mentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement factor was 10 5 and 10 9 for 2,4-dinitrotoluene and Rhodamine 6G, respectively. Recently, Sheng et al [104] have fabricated ordered LB TeNWs film to further immerse in HAuCl 4 aqueous solution. After the reduction, the ordered Te-Au hetero NWs film was tested as a SERS substrate.…”
Section: One-dimensional Materials (Nanowires and Carbon Nanotubes)mentioning
confidence: 99%
“…Additionally, the Te-Au hetero NWs film exhibits excellent uniformity and flexibility. Interestingly, a test using a polarized laser indicated that the local field that dominates the SERS signal is perpendicular to the NW template in the axial direction, while the intensity is independent of the angle of polarized light for the disordered film [104].…”
Section: One-dimensional Materials (Nanowires and Carbon Nanotubes)mentioning
confidence: 99%